Gaining Institutional Efficiency in the General Education Assessment for Technology Program Accreditation - ASM Delowar Hossain (Intelektual Pustaka Media Utama, 2015)
This work addresses the need to merge various student learning assessment activities to gain efficiency. Specifically, it discusses a mechanism of institutional assessment efficiency through development of common instruments for general education assessment that can support more than one accreditation requirement.